Haggadah in early Judaism and the New Testament - Aus, Roger David (Wissenschaftliche Untersuchungen zum Neuen Testament, 2021)
"Although it is difficult to define Haggadah exactly, this topic, thus far neglected in New Testament studies, can comprise among other things hyperbole; the addition of names, dates and numbers to an earlier text; glorification of a biblical character; parables to illustrate a statement or principle; and the creation of speeches, even of entire scenes. In addition, it is important in resolving the centuries-old inaccurate alternative of true or false, historical or fictional. The nineteen essays collected in this volume, by leading scholars in their own fields, illustrate in an exemplary way how Jews in Antiquity and Jewish Christians creatively employed haggadic elements in their writings."--